Between Star and Non-Star Accommodation: Governing Uneven Development in an Emerging Destination - Mayang Fitri Anggani; Pudin Saepudin; Ita Maemunah (Journal of Tourism Sustainability, 2026)
This study problematizes the persistent structural imbalance between star-rated and non-star accommodations in Subang Regency, West Java—a strategically positioned yet emerging tourism destination. Moving beyond traditional market-driven explanations, this research employs a qualitative case-study approach, integrating semi-structured interviews with key institutional actors and rigorous document analysis. The findings reveal that uneven development is not merely a byproduct of spatial characteristics or demand fluctuations, but is actively produced and mediated by complex governance configurations. Specifically, the study identifies how land-tenure complexities involving state-owned enterprises (PTPN), rigid zoning thresholds, and environmental mandates act as institutional filters that dictate investment feasibility and access. In response, local government necessitates adaptive, multi-layered strategies to navigate these structural bottlenecks. By conceptualizing governance as a mediating force rather than a neutral regulatory framework, this study contributes to the literature on emerging destinations by highlighting the necessity of institutional alignment to bridge the development gap and foster sustainable, balanced growth.